NanoSOSG: A Nanostructured Fluorescent Probe for the Detection of Intracellular Singlet Oxygen. Issue 11 (2nd February 2017) - Ruiz‐González, Rubén; Bresolí‐Obach, Roger; Gulías, Òscar; Agut, Montserrat; Savoie, Huguette; Boyle, Ross W.; Nonell, Santi; Giuntini, Francesca
Abstract: A biocompatible fluorescent nanoprobe for singlet oxygen ( 1 O2 ) detection in biological systems was designed, synthesized, and characterized, that circumvents many of the limitations of the molecular probe Singlet Oxygen Sensor Green ® (SOSG). This widely used commercial singlet oxygen probe was covalently linked to a polyacrylamide nanoparticle core using different architectures to optimize the response to 1 O2 . In contrast to its molecular counterpart, the optimum SOSG‐based nanoprobe, which we call NanoSOSG, is readily internalized by E. coli cells and does not interact with bovine serum albumin. Furthermore, the spectral characteristics do not change inside cells, and the probe responds to intracellularly generated 1 O2 with an increase in fluorescence. Abstract : Small particles, big improvement : When bound to nanoparticles (gray sphere), the cell‐impermeable fluorescent probe Singlet Oxygen Sensor Green (SOSG; green circles) escapes protein sequestration, readily undergoes cell uptake, and efficiently reports on variations in intracellular singlet oxygen levels.